2017
DOI: 10.1039/c7cp02071f
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the aqueous chemistry of glyoxal oxidation with hydrogen peroxide using molecular imaging

Abstract: Aqueous surfaces after photochemical and dark reactions of glyoxal and hydrogen peroxide (HO) have been studied using a microfluidic reactor coupled with an in situ liquid time-of-flight secondary ion mass spectrometry (ToF-SIMS) for the first time. Spectral principal component analysis was used to determine similarities and differences among various photochemical aging and dark reaction samples and controls. Compared with previous results using bulk solutions, our unique liquid surface molecular imaging appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 48 publications
2
37
1
Order By: Relevance
“…For UV aging, the device was set 10 cm away from a light source. 30 As soon as the desired aging time was reached, the device was immediately put into ToF-SIMS for analysis. More detailed information is described in Supplementary Methods.…”
Section: Salvi Enabled Liquid Sims Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For UV aging, the device was set 10 cm away from a light source. 30 As soon as the desired aging time was reached, the device was immediately put into ToF-SIMS for analysis. More detailed information is described in Supplementary Methods.…”
Section: Salvi Enabled Liquid Sims Characterizationmentioning
confidence: 99%
“…We recently demonstrated that in situ liquid SIMS can be used to study the a-l interface in photochemical ultraviolet (UV) aging conditions simulated by the vacuum-liquid interface. 30,31 Furthermore, weak interaction formation, such as ion pairs and ion solvation at the interface was monitored by in situ liquid SIMS. 32 We explore interfacial chemistry relevant to aqSOA formation in dark aging in this work ( Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, oxalic acid and tartaric acid were more likely to be observed in liquid samples. In addition, oligomers formed from hydration products, including C 6 H 9 O 7 + (m/z + 193), C 6 H 9 O 9 + (m/z + 225), C 8 H 15 O 13 + (m/z + 319), C 12 H 17 O 15 + (m/z + 401), and C 14 H 21 O 17 + (m/z + 461) in the positive mode and C 4 H 9 O 8 − (m/z − 185), C 6 H 7 O 9 − (m/z − 223), C 8 H 9 O 10 − (m/z − 265) in Figure , C 9 H 11 O 12 − (m/z − 311), and C 14 H 14 O 15 − (m/z − 422) in Figure in the negative mode, were observed in wet samples . In contrast, oligomers formed from dehydrated products were found in the dry surface analysis, such as C 8 H 9 O 12 + (m/z + 297), C 10 H 13 O 12 + (m/z + 325), and C 8 H 9 O 12 − (m/z − 297).…”
Section: Resultsmentioning
confidence: 99%
“…PCA has been applied for processing the ToF-SIMS data in the research of many fields, such as materials, biology, and medicine. [26][27][28][29][30][31][32] In this study, we collected atmospheric aerosols on different air quality level days of each season in 2015 in an urban area of Beijing and analyzed these aerosols by ToF-SIMS. Since winter is the season with most frequent haze, we compared the mass spectral aerosol data acquired on various pollution level days in winter and analyzed by PCA.…”
Section: Funding Informationmentioning
confidence: 99%
“…Using PCA, the most useful and significant information can be effectively extracted. PCA has been applied for processing the ToF‐SIMS data in the research of many fields, such as materials, biology, and medicine …”
Section: Introductionmentioning
confidence: 99%